2016
DOI: 10.1186/s12967-016-0949-y
|View full text |Cite
|
Sign up to set email alerts
|

HBx-induced MiR-1269b in NF-κB dependent manner upregulates cell division cycle 40 homolog (CDC40) to promote proliferation and migration in hepatoma cells

Abstract: BackgroundOccurrence and progression of hepatocellular carcinoma (HCC) are associated with hepatitis B virus (HBV) infection. miR-1269b is up-regulated in HCC cells and tissues. However, the regulation of miR-1269b expression by HBV and the mechanism underlying the oncogenic activity of miR-1269b in HCC are unclear.MethodsReverse transcription quantitative PCR (RT-qPCR) was used to measure the expression of miR-1269b and target genes in HCC tissues and cell lines. Western blot analysis was used to assess the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 32 publications
0
29
0
Order By: Relevance
“…29 NF-κB activated the transcription of miR-1269b and then resulted in promoting HCC cell cycle, proliferation and migration. 12 CDC40 was proved to be a target of miR-1269b, promoting malignancy of HCC. 12 Another study showed that TGF-β activated miR-1269 via Sox4 and positively feedback the TGF-β signaling by targeting Smad7 and HOXD10.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…29 NF-κB activated the transcription of miR-1269b and then resulted in promoting HCC cell cycle, proliferation and migration. 12 CDC40 was proved to be a target of miR-1269b, promoting malignancy of HCC. 12 Another study showed that TGF-β activated miR-1269 via Sox4 and positively feedback the TGF-β signaling by targeting Smad7 and HOXD10.…”
Section: Discussionmentioning
confidence: 99%
“…12 CDC40 was proved to be a target of miR-1269b, promoting malignancy of HCC. 12 Another study showed that TGF-β activated miR-1269 via Sox4 and positively feedback the TGF-β signaling by targeting Smad7 and HOXD10. 5 In lung cancer, miR-1269 might promote cell survival and proliferation by targeting TP53 and caspase-9.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The HBx protein has been associated with hepatocellular carcinogenesis because it sustains HBV replication, 71 interacts and inhibits p53 tumor suppressor, increases telomerase reverse transcriptase (TERT) expression, 72 and promotes invasiveness and metastasis in hepatitis B virus-related HCC. 73,74 HBx does not directly bind to DNA, but regulates transcription factors such as NF-κB), 75 the activator protein 1 (AP-1), 76 cAMP response element-binding protein (CREB), 46 and the coactivator CPB/p300, through which it could upregulate NOTCH target genes, but this still requires further validation ( Figure 3A).…”
Section: Hbx Proteinmentioning
confidence: 99%
“…HBx does not directly bind to DNA, but regulates transcription factors such as NF‐κB), the activator protein 1 (AP‐1), cAMP response element‐binding protein (CREB), and the coactivator CPB/p300, through which it could upregulate NOTCH target genes, but this still requires further validation (Figure A).…”
Section: Introductionmentioning
confidence: 99%